Variation in the production of enzymes by different isolates of Myrothecium roridum causing leafspot of mungbean - P. SHUKLA, S.N. SINGH and (Indian Phytopathology, 2002)
All 3 isolates of M. roridum (A-13, B-4 and C-45) exhibited considerable differences from each other in the production of cellulolytic and pectolytic enzymes in vitro as well as in vivo. Maximum production of cellulase (Cx) and polygalacturonase (PG) were recorded in isolate A-13 followed by isolates B-4 and C-45, while polymethylgalacturonase (PMG) was found in greater amounts in isolate C-45 followed by isolate A-13 and B-4. Maximum loss of viscosity in cellulase (Cx), polymethylgalacturonase(PMG) and polygalacturonase(PG) was observed in all the isolates after 80, 60 and 40 minutes, respectively, and then remained constant.